The Difference between Placebo and Energy Drinking Consumption towards Aerobic Endurance - Zarwan, Zarwan; Hardiansyah, Sefri; Zalindro, Ade; Maifitri, Fella (Sains Humanika, 2020)
An issue of this research is the aerobic endurance of students categorized low during the formation of physical conditions so that many students consume energy drinks to improve the aerobic endurance capability.Â However, this is still an assumption needed to prove by giving another comparative drink (placebo). The purpose of this research is to compare the effect of placebo and energy drinks consumption to aerobic endurance capability. Â It was quasi-experiment research using two types of substances: placebo consumed by experimental group (X1) and energy drinks consumed by the control group (X2). The population of this study was a group of 40 students. Samples were 36 students chosen by purposive sampling technique. Division of the group in a random way, the instrument used was Cooper run test 2.4 km. Data were analyzed using the test of different independent samples. The results of this study obtained the mean of 1.03 for the placebo group and the mean of 1.10Â for the energy drink group. The statistical testobtainedtobserved0.14 <ttable1.69 so that it can be concluded that the effects given by the consumption of placebo and energy drinks are not significantly different.